Karcinom Merklovih celic - Beigot, Franc (Zdravniški vestnik, 2020)
Background: Merkel cell carcinoma (MCC) is a rare, aggressive and often lethal neuroendocrine skin cancer. It can clinically resemble a benign skin lesion. Merkel cell cancer removal in the family medicine practice is a rare report in the literature. Case report: This report describes the removal of Merkel cell carcinoma less than 1 cm of size on the right wrist of an 80-year-old woman, affected by stroke; the initial clinical impression of the lesion was consistent with an inflammed cyst. Immediately after the incision, it was clear that it was a solid tumour, whish was then completely excised and sent to the pathologist. The result was MCC, the edges and the bottom of which had not been radically excised from the healthysurrounding tissue. The patient was immediately referred to the oncologist for further treatment, but she refused further treatment. Four years and 9 months after removal of the tumour, there are no clinical signs of local recurrence or signs of systemic progression. Conclusion: A family doctor who works in remote rural areas, more often than other dostors at the primary level have to use surgical skills. In addition, it can encounter rare aggressive malignant skin tumours. The solution is to confirm the diagnosis by pathohistological examination, followed by interdisciplinary treatment.
Keywords: družinska medicina; excision of skin tumor; family medicine; izrez kožnega tumorja; karcinom Merklovih celic; Merkel cell cancer